Degradation of sulfachloropyridazine by UV-C/persulfate: kinetics, key factors, degradation pathway. Issue 9 (4th June 2020) - Dan, Jiabin; Wang, Qiongfang; Mu, Kun; Rao, Pinhua; Dong, Lei; Zhang, Xin; He, Zedi; Gao, Naiyun; Wang, Jincheng
Abstract : Antibiotics are frequently detected in water, which can pose a great threat to human health. Abstract : Antibiotics are frequently detected in water, which can pose a great threat to human health. In this paper, an ultraviolet/persulfate (UV-C/PS) advanced oxidation process was utilized to remove a common antibiotic sulfachloropyridazine (SCP) efficiently from groundwater. The degradation mechanism and kinetics were investigated by researching several key influencing factors, including two radical scavengers ( tert -butanol and methyl alcohol), dosages of PS, initial pH, anions (H2 PO4 −, HPO4 2−, Cl −, HCO3 − and NO3 − ) and natural organic matter. The degradation of SCP followed a pseudo-first-order kinetic model and better degradation was achieved in acidic conditions than in alkaline conditions. The effect of scavengers indicated that both SO4 − ˙ and HO˙ contributed to the degradation of SCP and SO4 − ˙ played a major role. The degradation rate constants of SCP with SO4 − ˙ and HO˙ at the initial pH of 6.3 were calculated to be k SCP, HO˙ = 0.867 × 10 9 M −1 s −1 and k SCP, SO4 − ˙ = 3.073 × 10 9 M −1 s −1 in the UV-C/PS system by the relative rate method. Increasing the concentration of PS obviously facilitated the degradation and mineralization rates of SCP, which could reach 100% and 90%, respectively, at a PS dosage of 4.0 mM after 2 h. Also, H2 PO4 − and Cl − promoted the degradation of SCP, whereas the removal of SCP was restrained by the addition of HPO4 2−, HCO3 − and large dosages of NO3 − . The proposed degradation pathway of SCP was obtained by analyzing the intermediates.